ANALYSIS OF ACADEMIC SUPERVISION COMPETENCE THROUGH WORKSHOP ACTIVITIES (Case Study of Kapuas District Islamic Religious Education Teachers) - Soro, Suharyanto. H; Handayani, Sri; Bidin, Bidin; Rus'ansyah, Rus'ansyah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Quality learning is a stipulation to achieve the educational goal. That is why academic supervision is needed, one of the conscious efforts made to improve teacher competence so that teachers can develop a higher-quality learning process. This research aims to determine whether the workshop implementation can increase academic supervision competence so that it contributes positively to improving the learning process. This research used a case study approach. Methods of data collection using observation and interviews. The sample was selected based on purposive sampling. The results of the study indicated that if the workshop activity is carried out based on proper planning and implementation in accordance with the principles of the workshop itself, it can increase the competence of academic supervision to add experience to the supervisor himself. In other words, the supervisors and teachers participating in the workshop activities each gain new knowledge for the teacher and new experiences for the supervisor.